G513(P) Developing a framework of staff support across a paediatric hospital: the support (Supporting Paediatric Staff, Patients and Families to be One Resilient Team) programme. (25th October 2020) - Macaulay, CP; Conniff, H
Abstract : Aims: Paediatrics is one of the most diverse and rewarding fields of medicine but also brings with it unique medical and ethical challenges. We also care for increasingly complex medical patients and are faced with ethical dilemmas that can lead to conflict with families and a challenging work environment: it can be emotionally exhausting. At our tertiary children's hospital we became aware that this was having a negative impact on our staff's wellbeing and ability to care for our patients. In particular we recognised that staff were being exposed to distressing events and then expected to continue with clinical work with no formal system to debrief or acknowledge the impact of these events. We aimed to do something to address this. Methods: We established a working group of senior nurses, executive members, Paediatricians and Psychologists to identify issues and implement change through our SuPPORT programme. Within this, we created a staff support psychologist (PSS) role (0.3 WTE) to establish a psychological debrief pathway, coordinate and run debriefs and establish/scope other supports e.g. reflective practice. Results: The group has created a staff support 'pyramid', developing new resources and bringing together activities which were already in place. This includes a robust debrief pathway following serious incidents, and Paediatric Schwartz rounds. The PSS role has been central in this process. Since the role began we have run regular reflective practice sessions in several areas, and held 71 psychology mediated debriefs. Feedback from staff has been hugely positive. Conclusion: By establishing this programme we have acknowledged that staff may feel overwhelmed by the complex medical and ethical situations in paediatric care. We are still in the early stages, but staff report feeling a different 'culture' of support at work. Crucial to this has been the commitment by our senior leadership team. We recognise that these problems are not unique to our hospital and have had interest from other hospitals in spreading this model.